Penyuluhan Pengaruh Desain Grafis Terhadap Digital Marketing Karang Taruna Aksara RW 17 Kelurahan Pancoran Mas - Depok - Maria Valentine, Hany; Ramos, Samuel (HIMPUNAN DOSEN GEMILANG INDONESIA, 2022)
Nowadays, social media users in Indonesia are increasing rapidly, this is a very good opportunity for business people to market their products. This community service activity is carried out at Karang Taruna Aksara RW17 which is located in Pancoran Mas-Depok Village, where residents in the village have several UMKM businesses such as handicrafts, various snacks, and various other creatures. However, the marketing method of UMKM business actors is still carried out offline, only residents know and buy products from UMKMs in Pancoran Mas-Depok Village. Based on these problems, this community service activity was carried out to provide counseling on the influence of graphic design on digital marketing to the youth of Karang Taruna Aksara RW17 to support product marketing for UMKM business people in Pancoran Mas-Depok Village. The form of activity from this training uses a dialogical collaborative-participatory approach method in the form of lectures, questions and answers, interactive discussions for the delivery of material, and direct practice using a laptop connected to the network. There are 3 stages in the training, including 1) preparation, 2) implementation, and 3) reporting. The results of the training showed high enthusiasm from the participants, and are expected to help UMKM business people in marketing their products digitally, both on social media and on marketplaces